Biomorphic Silicon Carbide from Malaysian Hardwood - Leha Abdul Rahman, Noor; Mei Hyie, Koay; Kalam, Anizah; Md Yusof, Fauziah (International Journal of Engineering and Technology, 2018)
Porous silicon carbide with mimicking the original microstructure of wood are prepared by pyrolysis and subsequently impregnated with silicon by silicon melt infiltration. The infiltration process was performed at 1500 Â°C for 3 hours holding times in inert atmosphere. Two types of wood were used as precursor which is Kapur and dark red Meranti.The morphology of resulting porous SiC have been investigated using scanning electron microscope (SEM/EDX) and X-ray diffraction (XRD) analysis. The density of the samples was characterized by Archimedes methods. The excess of silicon was removed by etching with the mixture of hydrofluoric and nitric acid. The flexural strength was tested by the three-point flexural method at room temperature.It has been shown that the final SiC for both precursors have similar density. The existence of SiC was proved by the XRD result, whereas EDX analysis of silicon content revealed that the formation of silicon carbide in dark red Meranti is higher than that of Kapur. The flexural strength and modulus of dark red Meranti samples were much higher than those of the kapur samples because of higher formation of silicon carbide in dark red Meranti.Â Â